“Between Cultural Norms and Economic Survival: Navigating Egyptian Lower and Middle Income Women’s Challenges in the Informal Versus the Formal Work: “A Case Study from Cairo” - Abdelnazer, Rowan Mahmoud (AUC Knowledge Fountain, 2026)
This study investigates the ongoing gender inequities experienced by low and middle-income women in Egypt’s formal and informal labor economy, specifically it is based in Cairo. Although there are many advances made globally on women's rights, yet women still face great challenges such as discrepancies in salary, fewer leadership roles and cultural expectations which put child-bearing duties before professional growth. On the one hand, flexible work for women in developing countries is through informal sector, which makes them vulnerable and serves as a source of their exploitation and insecurity (e.g., lack of social security; workplace hazards), on the other hand, formal jobs are subject to glass ceiling phenomenon along with maternity leave problem and discrimination. inclusive economic development. Ultimately, This study addresses literature gap which is comparative framework of inequalities across both sectors, this paper examines to what extent structural, social, and policy factors especially cultural norms, education, and level of legal protections enforcement within workplace perpetuates perpetuate inequities for women. This study uses qualitative study, through conducting in-depth semi-structured interviews with low-income and middle income participating in formal and informal sectors.